HIPGEN: a randomized, multicentre phase III study using intramuscular PLacenta-eXpanded stromal cells therapy for recovery following hip fracture arthroplasty <subtitle>a study design</subtitle> - Tobias Winkler; Matthew L. Costa; Racheli Ofir; Ornella Parolini; Sven Geissler; Hans-Dieter Volk; Christian Eder (Bone & Joint Open, 2022)
Aims The aim of the HIPGEN consortium is to develop the first cell therapy product for hip fracture patients using PLacental-eXpanded (PLX-PAD) stromal cells. Methods HIPGEN is a multicentre, multinational, randomized, double-blind, placebo-controlled trial. A total of 240 patients aged 60 to 90 years with low-energy femoral neck fractures (FNF) will be allocated to two arms and receive an intramuscular injection of either 150 × 106 PLX-PAD cells or placebo into the medial gluteal muscle after direct lateral implantation of total or hemi hip arthroplasty. Patients will be followed for two years. The primary endpoint is the Short Physical Performance Battery (SPPB) at week 26. Secondary and exploratory endpoints include morphological parameters (lean body mass), functional parameters (abduction and handgrip strength, symmetry in gait, weightbearing), all-cause mortality rate and patient-reported outcome measures (Lower Limb Measure, EuroQol five-dimension questionnaire). Immunological biomarker and in vitro studies will be performed to analyze the PLX-PAD mechanism of action. A sample size of 240 subjects was calculated providing 88% power for the detection of a 1 SPPB point treatment effect for a two-sided test with an α level of 5%. Conclusion The HIPGEN study assesses the efficacy, safety, and tolerability of intramuscular PLX-PAD administration for the treatment of muscle injury following arthroplasty for hip fracture. It is the first phase III study to investigate the effect of an allogeneic cell therapy on improved mobilization after hip fracture, an aspect which is in sore need of addressing for the improvement in standard of care treatment for patients with FNF. Cite this article: Bone Jt Open 2022;3(4):340–347.